Over a million students use our free study notes to help them with their homework
x2+2x+1=0, (x+1)(x+1)=0, (x+1)2=0. So x=-1
f'(x)=( sqrt (x^2+1) - x * ( x / sqrt (x^2 +1) ) ) / (x^2+1) = (x^2 + 1 + x^2) / ( (x^2 + 1) * sqrt ( x^2 + 1) ) = 1 / ( (x^2 + 1) * sqrt (x^2 + 1) ).
f'(x) > 0 for any x => f is increasing...
The point of intersection is where the lines would cross if we drew them on the same graph, in your exam you may be asked to find the coordinates of this point.
To do this we would first draw a ske...
x2+5x+6=0 (x+3)(x+2)=0 x=-3 and x=-2
To solve the equation first collect all the unkown terms (letters) on one side and the known terms (numbers) on the other. Remember you must do the same to both sides to keep it balanced. First remove the...
←
659
660
661
662
663
→
Internet Safety
Payment Security
Cyber
Essentials